Fluorescence sensing of nitrophenol explosives using a two-dimensional organic–metal chalcogenide fully covered with functional groups. Issue 29 (21st March 2022) - Pan, Yu; Wang, Chengpeng; Fu, Zhihua; Wang, Guang-E; Xu, Gang
Abstract : A new fluorescent OMC, few-layered CdClHT, fully and orderly covered with phenol groups shows superb performance toward TNP. Abstract : A new 2D fluorescent organic–metal chalcogenide (OMC), CdClHT (HT = 4-hydroxythiophenol), evenly covered with phenol groups is reported. CdClHT represents unparalleled selectivity and the highest sensitivity towards 2, 4, 6-trinitrophenol (TNP) ( K SV = 2.16 × 10 7 m −1, experimental LOD = 2 nM), among all reported 2D conjugated polymer (CP) luminescent detectors.